Non-local quantum interference of deterministically separated photons - Kiran Bajar; Vikas S. Bhat; Rounak Chatterjee; Tabish Qureshi; Sushil Mujumdar (Results in Optics)
Quantum entanglement enables a wide range of fundamental studies and practical applications in quantum optics, computing, and communication. In this work, we investigate two-photon interference using position-momentum entangled photons generated via Type-II Spontaneous Parametric Down-Conversion (SPDC). By employing a double-slit setup, we explore two distinct quantum interference phenomena: the Hanbury Brown and Twiss (HBT) effect, where the photons pass through different slits, and NOON-state interference, where both photons traverse the same slit. We deterministically separate the two photons based on their orthogonal polarizations and demonstrate that both interference effects persist despite their distinguishability at the detectors. This result goes beyond the conventional understanding of two-photon interference and reveals a novel nonlocal HBT effect, where interference occurs even in the absence of spatial overlap, and is rooted in entanglement. Our findings deepen the understanding of quantum interference and open new avenues for applications in quantum optics and precision measurement.